2017
DOI: 10.1111/pedi.12538
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and glycemic control in adolescents with type 1 diabetes

Abstract: Our study suggests that poor sleep quality is associated with increased HbA1c in adolescents with type 1 diabetes and that higher levels of circadian misalignment are associated with increased insulin requirements. If replicated, our results indicate a clinical relevance of sleep habits in adolescents with type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 34 publications
10
43
0
1
Order By: Relevance
“…42,45,5 However, some data have supported that delays or disruptions in sleep may be linked to poor glycemic control, diabetes-related complications, and inconsistent diabetes management. 39,41,51,52 For instance, Pillar et al 39 found that a swift decline in glucose levels paralleled more PSG-recorded awakenings in children with T1DM. Supporting these findings, higher HbA1c, DKA, and more frequent hypoglycemic episodes were more likely to have been experienced by children with a higher severity of parent-reported sleep disturbances, but the number of fingersticks did not associate with sleep disturbance severity.…”
Section: Sleep Disturbancesmentioning
confidence: 99%
“…42,45,5 However, some data have supported that delays or disruptions in sleep may be linked to poor glycemic control, diabetes-related complications, and inconsistent diabetes management. 39,41,51,52 For instance, Pillar et al 39 found that a swift decline in glucose levels paralleled more PSG-recorded awakenings in children with T1DM. Supporting these findings, higher HbA1c, DKA, and more frequent hypoglycemic episodes were more likely to have been experienced by children with a higher severity of parent-reported sleep disturbances, but the number of fingersticks did not associate with sleep disturbance severity.…”
Section: Sleep Disturbancesmentioning
confidence: 99%
“…Specifically, adults displaying frequent swings between insufficient sleep and sleep compensation had higher insulin requirements than those with lower sleep variability, highlighting the importance of sleep regularity in the management of diabetes, though behavioral substrates that may impact both sleep patterns and diabetes care, such as executive function, were not assessed [•18]. A separate study of sleep patterns in adolescents with T1D using questionnaire data revealed that the mean variability in weekday/weekend sleep timing was 2.5 hours, and this variability was significantly associated with increased insulin requirements, regardless of adherence to treatment [19]. These findings support that sleep variability has negative effects on glycemic control in both adults and adolescents with T1D.…”
Section: Sleep Patterns and Disturbances In T1dmentioning
confidence: 99%
“…To date, the T1D literature has provided some support for a general sleep pathway affecting executive function and T1D adherence in the short term, and health complications in the long term, such as diabetic ketoacidosis (DKA) and higher HbA1C levels (Figure ). Some research suggests that adolescents with greater sleep disturbances and lower sleep quality, have poorer T1D management and higher HbA1C levels . Moreover, one study has shown that the additive effect of poor self‐reported sleep relates to higher HbA1c levels, more episodes of severe hypoglycemia, and more episodes of DKA in youth …”
Section: Conceptual Modelsmentioning
confidence: 99%
“…31 The emerging literature examining sleep and T1D warrants a Figure 1). Some research suggests that adolescents with greater sleep disturbances and lower sleep quality, 33 have poorer T1D management and higher HbA1C levels. 34 Moreover, one study has shown that the additive effect of poor self-reported sleep relates to higher HbA1c levels, more episodes of severe hypoglycemia, and more episodes of DKA in youth.…”
Section: Type 1 Diabetes and Sleepmentioning
confidence: 99%